Phytochemical screening, antiproliferative evaluation, and molecular docking studies of Acacia nilotica fruit from Nigeria - Anthony, William Ojoniko; Okpala, Ejike Onwudiegwu; Obiyenwa, Kehinde Gabriel; Eneogwe, Godfrey Okechukwu; Semire, Banjo (Eclética Química, 2024)
Acacia nilotica, (Fabaceae), is valued for its medicinal properties. We examine the antiproliferative properties of the aqueous fruit extract of A. nilotica. Aqueous extract from Acacia has been associated with potential anticancer effects in fruits and vegetables through screening, antiproliferative, and molecular docking evaluation. Phytochemical screening reveals the presence of alkaloids, saponins, tannins, flavonoids, steroids, and carbohydrates. The extracts showed significant antiproliferative effects at eight concentrations (8–50 mg mL–1) examined in comparison to the standard (methotrexate). When compared to Sorghum bicolor seed radicles treated with methotrexate at 48, 72, and 96 h, 50 mg mL–1 extract significantly inhibited the generation of seed radicals, with potent inhibitions of 87.06, 83.48, and 81.45%. Analysis of molecular docking results showed that [(2R,3S)-2-(3,4-dihydroxyphenyl)-3,5-dihydroxy-3,4-dihydro-2H-chromen-7-yl]3,4,5-trihydroxybenzoate (D21), (5R,9R,10R,13S,14S,17S)-17-[(2S,4R)-4-[(2S)-3,3-dimethyloxiran-2-yl]-4-hydroxybutan-2-yl]-4,4,10,13,14-pentamethyl-1,2,5,6,9,11,12,15,16,17-decahydrocyclopenta[a]phenanthren-3-one (D28) and [(2R,3S)-2-(3,4-dihydroxyphenyl)-3,7-dihydroxy-3,4-dihydro-2H-chromen-5-yl] 3,4,5-trihydroxybenzoate (D29) have strong tendency to inhibit dihydrofolate reductase (1VDR), capase-9 (6J15) and Mycobacterium tuberculosis (Mtb) (6J17) better than methotrexate and azacitidine, known antiproliferative drugs. These findings support the use of A. nilotica in traditional medicine for the treatment of tuberculosis and cancer.